MINING PROCEDURES AND ENVIRONMENTAL PROTECTION IN ROMANIA. BETWEEN ECONOMICAL BENEFITS AND SUSTAINABLE DEVELOPMENT – A CASE STUDY - Barbu, Ilie Adrian (Journal of Advanced Research in Law and Economics; Vol 1 No 2 (2010): JARLE volume 1 Issue 2(2) Winter 2010, 2017)
Sustainable Development is, at this point, one of the most often used expression in everything regarding the environmental protection and the development of the human society. The Environmental European legislation and the legislations of the member countries consider it as the only solution for satisfying the economical development and the needs of the human society, but containing an healthy environment, thus are builded around this as a base principle. So every environmental aspect of the economical development is regulated by legislation that helps empowering this principle. This also applies into mining field, but such work involves a variety of legal, economic and social issues. By analyzing these issues, the conclusion is that a strong and forced economic development is not always bringing the greatest benefit to human communities, because there are certain sacrifices that sometimes are too big to be made.
Keywords: sustainable development, environmental legislation, mining legislation, Rosia Montana, gold cyanidation, environmental agreement, urbanism certificate, archaeological discharge certificate